Alleviation of catching and crating stress by dietary supplementation of Bacillus subtilis in Pekin Ducks - Mitin, Helen; Zulkifli, Idrus; Che Jamri, Muhammad Hazim; Zamzuri, Nur Athirah; Samian, Nurain Aliah; Hussein, Aimi Nabilah; Yong, Meng Goh; Sazili, Awis Qurni (Multidisciplinary Digital Publishing Institute, 2022)
Catching and crating may elicit stress and fear reactions in poultry because the procedures involve human contact and exposure to a novel environment. This study determined the effects of dietary probiotic supplementation on physiological stress, underlying fear, and growth performance of Pekin ducks subjected to catching and 4 h of crating. The study used a 2 × 2 factorial arrangement; the main factors were diet (basal or basal + probiotic) and crating durations (0 or 4 h). From 1 to 21 days of age (doa), birds were fed a basal or basal + probiotic (CLOSTAT® (Bacillus subtilis) (Kemin Industries, Inc., Des Moines, IA, USA), 1 g/kg) diet. At 21 doa, an equal number of ducklings from each dietary group were caught and crated for 4 h or left undisturbed in the home pens. Birds were examined for serum corticosterone (CORT), heat shock protein (HSP) 70, creatine kinase (CK), triglyceride (TG), glucose (GLU), cholesterol (CHOL), and lactate (LAC) concentrations, heterophil to lymphocyte ratios (HLR), tonic immobility (TI) duration, open-field (OF) test, body weight (BW), and feed conversion ratios (FCR). Diet had no significant (p > 0.05) effect on CORT among the non-crated ducks. However, after catching and crating, birds fed the control diet had significantly (p < 0.05) higher CORT than their probiotic-supplemented counterparts. Catching and crating significantly (p < 0.05) elevated HSP70, HLR, GLU, and CHOL but reduced TG in ducks. Birds fed the probiotic-supplemented diet showed significantly (p < 0.05) lower HSP70, HLR, TG, and CK than those fed the control diet. Probiotic-supplemented ducks showed reduced fear-related behaviours, including TI durations, ambulation latency, and body shaking. Diet had a negligible effect on body weights and FCR of ducks at 21 doa. In brief, catching and crating for 4 h augmented Pekin ducks’ physiological stress and fear reactions, and supplementing birds with probiotics was beneficial in ameliorating these detrimental effects.